Educational reform in engineering: understanding struggles of students in solid mechanics - Siong, Wee Lee; Mohamad, Nor Mayuze; Jamal, Mohammad Hazizi; Abu Bakar, Azinoor Azida (UiTM Cawangan Johor, 2025)
The Diploma in Civil Engineering Programme (CEEC110) offered by Universiti Teknologi MARA is an accredited engineering technician education programme approved by the Engineering Technology Accreditation Council (ETAC), Malaysia. ETAC requires students to satisfy a minimum requirement of scoring at least 50% in each Programme Outcome (PO) by the end of their candidature. Monitoring of PO and Course Outcomes (CO) at the course level is conducted every semester, and the current situation has revealed a cause for concern regarding the attainment of CO-PO in the Solid Mechanics course. Therefore, this study aims to identify the lowest achievement of CO-PO in the Solid Mechanics course and its corresponding assessment. Results show that the attainment of CO2-PO2 is the lowest in the final exam assessment throughout the studied semesters. Syllabus contents under CO2-PO2 (statically determinate beam) were discussed, and a case study was conducted to investigate the reasons for poor performance in solving problems related to beam questions in the final exam. Subsequently, effective teaching and learning of Solid Mechanics are discussed, and suggestions on strategies to improve students' final exam scores are made.